2017
DOI: 10.1212/wnl.0000000000004415
|View full text |Cite
|
Sign up to set email alerts
|

A natural history study of X-linked myotubular myopathy

Abstract: Objective:To define the natural history of X-linked myotubular myopathy (MTM).Methods:We performed a cross-sectional study that included an online survey (n = 35) and a prospective, 1-year longitudinal investigation using a phone survey (n = 33).Results:We ascertained data from 50 male patients with MTM and performed longitudinal assessments on 33 affected individuals. Consistent with existing knowledge, we found that MTM is a disorder associated with extensive morbidities, including wheelchair (86.7% nonambul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
89
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 15 publications
6
89
0
4
Order By: Relevance
“…Although the major cause of death in MTM has been shown to be respiratory complications, 3 neither of the present recipients had any respiratory complications, receiving some degree of respiratory support. Tracheostomy can also be useful for providing respiratory support in the perioperative period.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Although the major cause of death in MTM has been shown to be respiratory complications, 3 neither of the present recipients had any respiratory complications, receiving some degree of respiratory support. Tracheostomy can also be useful for providing respiratory support in the perioperative period.…”
Section: Discussionmentioning
confidence: 51%
“…Although previous studies described up to 50% of MTM patients dying in the first year of life and 90% dying by age 10, 2,12 a recent survey showed that the mean survival of MTM patients was 12 years and 2 months, which was longer than the predicted prognosis. 3,13 Furthermore, a longer prognosis was expected because Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In XLMTM, resultant lack or dysfunction of the myotubularin protein leads to severe, progressive skeletal myopathy . Affected boys experience respiratory failure and dysphagia and aspiration risk in early infancy, often requiring mechanical ventilation and feeding tubes . Neuromuscular weakness contributes to cumulative morbidities throughout childhood as well as high mortality rates from respiratory events.…”
Section: Introductionmentioning
confidence: 99%
“…highlight the importance of performing research on rare genetic diseases . Their retrospective X‐linked myotubular myopathy (XLMTM) study complements a recent natural history study done by the same group . The investigators reviewed 115 medical records of patients with XLMTM to better characterize disease manifestations and examine previous medical management.…”
mentioning
confidence: 99%